THE CHALLENGES FACED BY EFL PROSPECTIVE TEACHERS DURING TPACK DEVELOPMENT - Imadul Bilad; Lina Aris Ficayuma; Achmad Anang Darmawan (STKIP AL HIKMAH SURABAYA, 2022)
The high level of Technological Content Knowledge (TCK) among prospective student teachers in their TPACK profile has significant implications. This indicates that these students possessed a strong understanding of how to effectively integrate ttechnology into their teaching practices, specifically in relation to the content they were teaching. This proficiency in TCK enables them to utilize technological tools and resources in a purposeful and pedagogically sound manner, enhancing the overall quality of instruction in the classroom. As a result, these prospective teachers are better equipped to meet the demands of the digital age and provide meaningful and engaging learning experiences for their future students. However, it is important for them to continue developing their pedagogical and content knowledge along with their technological skills to ensure a comprehensive and well-rounded TPACK profile.